Low inclination circular orbits for remote sensing satellites - Kamalaldin, Karim; Okasha, Mohamed Elsayed Aly Abd Elaziz (Trans Tech Publications Ltd., Switzerland, 2014)
This paper investigates the design methodology of low Earth inclined circular orbits for remote sensing satellites to satisfy certain mission requirements and constrains such as coverage, resolution, illumination conditions and attitude maneuvers capabilities. Although sun synchronous orbit (SSO) proved to be a good candidate for most remote sensing applications due to its constant lighting conditions and global coverage, low inclined orbits are distinguished by long ground track especially if the target area of concern has horizontal rectangular border. With that respect, low inclined orbits may lead to improvement of the satellite imaging accessibility to the target area per day or reduction of satellite revisit time compared to SSO. This paper exploits these characteristics for low inclined orbits. The target area considered in simulation is between 220 and 320 N latitude lines with 2.5 m ground sample resolution. The satellite maximum rolling capability is 350 and the sun elevation angle is constrained between 300 and 700 for purpose of maximizing the quality of the obtained images. Matlab and STK software are employed to define the initial orbital parameters to meet these conditions for a low inclined orbit.